(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Candida albicans (C. albicans) has emerged as a potentially pathogenic fungus rather than benefit mucosal commensal in patients with pulmonary diseases. Although respiratory candidiasis secondary to pulmonary tuberculosis has been reported in the past, it has gained more relevance recently due to increased use of broad spectrum antibiotics and immunosuppressive drugs. Objective:To detect C. albicans in sputum samples from patients with pulmonary diseases using conventional and molecular methods. Methods: One hundred sputum samples obtained from patients with pulmonary symptoms were included in this study. Sputum samples were dispensed into three specimen parts; the first one was applicated for cultured on Sabouraud dextrose agar at 37 °C for 48 hrs and then the purified colony of Candida underwent biochemical tests including API Candida strips, and germ tube. The second part was undergone direct gram stain, while the third part was applicated for DNA extraction and then molecular diagnosis with PCR technique using specific primers. Results:Culture result revealed 43 positive samples for Candida species out of 100 samples. Among these positive samples, 23 (53.5%) were positive for C. albicans in each of culture, germ tube and API. Molecular test revealed an amplicon with 538bp fragment of phospholipase gene from the same 23 samples. Conclusion:C. albicans is highly prevalent among patients suffering from bronchopulmonary symptoms. The molecular and conventional methods gave concomitant results as detection tools for the diagnosis of such microorganisms. Keywords:Candida albicans, phospholipase B gene, sputum. DOI: 10.22578/IJMS.14.4.6